Assessing Postural Stability in Gastrointestinal Endoscopic Procedures with a Belt-like Endoscope Holder Using a MoCap Camera System - Durič, Tadej; Hejda, Jan; Volf, Petr; Sokol, Marek; Kutílek, Patrik; Hajer, Jan (Journal of personalized medicine, 2024)
Background/Objectives: As musculoskeletal injuries in gastroenterologists related to the performance of endoscopic procedures are on the rise, solutions and new approaches are needed to prevent these undesired outcomes. In our study, we evaluated an approach to ergonomic challenges in the form of a belt-like endoscope holder designed to redistribute the weight of the endoscope across the whole body of the practitioner. The aim of the study was to determine how the use of this holder affected the body posture of practitioners during endoscopy. Methods: We designed a special endoscopic model that emulates basic endoscopic movement and maneuvers. With the use of the MoCap camera system, we recorded experienced endoscopists exercising a standardized set of tasks with and without the holder. Results: Following video and statistical analyses, the most significant differences were observed in the position of the left arm which pointed to a more relaxed arm position. Conclusions: The ergonomic benefits of the belt holder in this model merit testing in the clinical setting to evaluate its effectiveness and prevention of musculoskeletal injuries in GI endoscopy.